Dark personality traits and problematic smartphone use: The mediating role of fearful attachment. (15th October 2019) - Balta, Sabah; Jonason, Peter; Denes, Amanda; Emirtekin, Emrah; Tosuntaş, Şule Betül; Kircaburun, Kagan; Griffiths, Mark D.
Abstract: Recently, empirical research has shown dark personality traits (i.e., Machiavellianism, psychopathy, narcissism, sadism, spitefulness) to be associated with problematic and addictive online behaviors. However, their direct relationships with problematic smartphone use (PSU) have yet to be examined. The present study investigated the direct and indirect associations of dark personality traits with PSU via fearful and dismissing attachment styles among 546 participants. Results indicated that men had higher scores on measures assessing dark personality traits and women had higher PSU. Narcissism and spitefulness were directly associated with PSU in the total sample, men, and women. Machiavellianism was indirectly associated with PSU via fearful attachment among men and sadism was directly and indirectly associated with PSU via fearful attachment among women. Findings suggest that dark personality traits may play a contributory role in higher PSU (with different traits having different effects among men and women), and that attachment styles partially explain the relationship between dark traits and PSU. Highlights: The relationship between dark traits and problematic smartphone use (PSU) was examined. Men had higher scores on dark personality trait measures and women had higher PSU. Narcissism and spitefulness were directly associated with PSU. Machiavellianism was indirectly associated with PSU via fearful attachment in men. Fearful attachment partially mediated the relationship between sadism and PSU in women.